Ten Reasons Why Canada Should Join the American Convention on Human Rights - Duhaime, Bernard (Revue générale de droit)

(untitled) (Éditions Wilson & Lafleur, inc., 2019)
The present contribution seeks to present comprehensively ten reasons why Canada should join the American Convention on Human Rights and recognize the compulsory jurisdiction of the Inter-American Court of Human Rights.